Upaya Nahdlatul Ulama dalam Melawan Kolonialisme dan Imperialisme pada Masa Pergerakan Nasional Indonesia 1926 – 1942 - Asiah, Nur; Subakti, Ganjar Eka (MISYKAT AL-ANWAR JURNAL KAJIAN ISLAM DAN MASYARAKAT, 2024)
In the 16th century European nations intensively carried out colonialism and imperialism. The Dutch also carried out this practice of colonialism and imperialism against the Indonesian people. This colonialism and imperialism of course made the Indonesian people suffer. This then became the reason for the resistance of the native people. This native resistance then gave birth to a national movement marked by the founding of the Budi Utomo organization or movement, which was then followed by the formation of other national movement organizations, one of which was Nahdlatul Ulama. This research aims to find out about NU efforts to fight colonialism and imperialism carried out by the Dutch during the national movement. This research uses a historical method using a literature study approach. NU efforts to fight colonialism and imperialism carried out by the Dutch were carried out in several fields, one of which was through the political field, namely by initiating the establishment of MIAI which is a federation of various Islamic religious organizations that in each of its activities is full of political activities to influence government political policies. Netherlands at that time. Then, in the socio-religious field, NU focused on promoting and spreading Islam, which at that time competed with the spread of Christianity by the Dutch government. Apart from that, in this field, NU also cultivated an attitude of nationalism through the spirit of jihad. Finally, in the field of education, NU established many educational institutions such as Islamic Boarding Schools, Private Schools, and Madrasas, which can compete with Western-style schools founded by the Dutch which could only be enjoyed by some groups.